Intravenous Dexamethasone as an Adjunct to Improve Labor Analgesia: A Randomized, Double-blinded, Placebo Controlled Clinical Trial. Issue 2 (June 2018) - Dube, P.; Mitra, S.; Singh, J.; Saroam, R.; Mehra, R.
Abstract : ( J Clin Anesth . 2017;43:6–10) It is well recognized that lumbar epidural analgesia using local anesthetic with or without an adjuvant is a consistently effective method of pain relief during labor. However, newer adjuvants, such as clonidine and neostigmine, are associated with adverse side effects and may be less suitable in pregnant women. A potential alternative is dexamethasone, a well-known anti-inflammatory drug. As there are limited studies regarding its intrapartum use, the authors of the present study evaluated the role of intravenous dexamethasone as an adjuvant to neuraxial analgesia for labor pain in a double-blind, prospective, randomized, placebo-controlled study.